1999
DOI: 10.1111/j.1740-8261.1999.tb00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reproductive Status on Feline Renal Size

Abstract: Renal length and width dimensions were determined from survey radiography and excretory urography in 28 cats of various sex and reproductive status. Renal dimensions were expressed as a ratio to the length of the second lumbar vertebra. Renal dimensions were not significantly different when males were compared to females. However, significant differences in renal dimensions between intact and neutered cats were identified. Renal length ratios for neutered cats were: left kidney 2.22 +/- 0.14 (mean +/- standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 8 publications
4
52
1
Order By: Relevance
“…However, no such difference was found in other dog breeds. Previous studies also reported inconsistent results: one study reported that kidney size was slightly larger in male dogs, another feline study reported that intact cats had larger kidneys, and another canine studies reported that there were no differences between sexes [4, 19, 20, 22, 28]. The results of this study and previous studies may indicate that sex has a minor effect on kidney size.…”
Section: Discussioncontrasting
confidence: 59%
“…However, no such difference was found in other dog breeds. Previous studies also reported inconsistent results: one study reported that kidney size was slightly larger in male dogs, another feline study reported that intact cats had larger kidneys, and another canine studies reported that there were no differences between sexes [4, 19, 20, 22, 28]. The results of this study and previous studies may indicate that sex has a minor effect on kidney size.…”
Section: Discussioncontrasting
confidence: 59%
“…The kidney lengths were compared to the length of a single lumbar vertebra (L2) measured from endplate to endplate by a single investigator (CLM) 2224. A ratio was calculated for each kidney; a range of 2–3 times the length of L2 was considered normal 3,22,23,2527. Cats with CKD were staged according to the IRIS guidelines5; without urine protein to creatinine ratios and blood pressure measurements, IRIS substaging was not possible in this study.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the potential influence of elevated steroid hormones on kidney size (Broulik , Shiroma and others , Lane ) in animals with ferret adrenal gland disease, the radiographic dimensions were compared between the subgroups of ferrets with and without the disease using a student's t ‐test.…”
Section: Methodsmentioning
confidence: 99%
“…The size of the kidneys can be impacted by other factors aside from pathology, such as age, sex and reproductive status (Korenchevsky and Dennison , Freudenberger and Howard , Kochakian , Broulik , Shukla and others , ‐Shiroma and others , Lane ). For example, kidneys have been shown to be larger in males than females in humans, rats, mice, hamsters and dogs (Lane ).…”
Section: Introductionmentioning
confidence: 99%